Personal Data Processing of Online Platforms’ and Search Engines’ Users: The case of the EU Digital Services Act - Farinho, Domingos Soares (Public Governance, Administration and Finances Law Review, 2024)
The new EU Digital Services Act (DSA) aims to regulate intermediary service providers and special attention is given to online platforms and search engines. The bulk activity of these two online players is personal data processing, under the guise of content moderation or recommendations to users. This means that both the EU GDPR and DSA interconnect when protection of personal data is concerned and it is the task of lawyers to determine how is the interplay between these two keys pieces of legislation in the EU digital domain. The paper sets out to try to understand how both EU Regulations connect and what is the end result. Beyond the introduction, section 2 describes how the GDPR applies to online platforms, focusing on grounds for lawful personal data processing. In section 3 the main interplay is presented and analysed and the normative relation between the GDPR and the DSA is assessed with special attention being given to specific data protection duties and prohibitions arising from the DSA and its regulatory framework.